The Moxon Tennyson a landmark in Victorian illustration - Cooke, Simon (Simon Gareth) (Athens : Ohio University Press, 2021)
Cooke's analysis of this milestone Victorian publication reveals the fluctuating harmony and dissonance between Tennyson's poems and their illustrations, the technical challenges and occupations involved in its manufacture, its readers' contemporary reception, and its subsequent influence as a variously revered and reviled publication.
Intro -- Contents -- Illustrations -- Acknowledgments -- Introduction -- 1: The Making of the Book -- 2: Painting, Time, Light, Landscape -- 3: Englishness, the Modern, Copying from Nature -- 4: Psychology, Dreaming, Medievalism -- 5: Relationships, Gender, Androgyny -- 6: Reception, Influence, Afterlife -- Appendix 1 -- Appendix 2 -- Notes -- Bibliography -- Index
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892. -- Illustrations; Moxon, Edward, -- 1801-1858.; Moxon, Edward, -- 1801-1858.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892. -- Illustrations; Moxon, Edward, -- 1801-1858; Poems (Tennyson, Alfred Tennyson, Baron); Illustration of books -- England -- 19th century; Literature publishing -- England -- History -- 19th century; Authors and publishers -- England -- History -- 19th century; Book design -- England -- History -- 19th century; Printing -- England -- History -- 19th century; Literature and society -- England -- History -- 19th century; Illustration des livres -- Angleterre -- 19e siècle.; Littérature -- Édition -- Angleterre -- Histoire -- 19e siècle.; Écrivains et éditeurs -- Angleterre -- Histoire -- 19e siècle.; Livres -- Conception graphique -- Angleterre -- Histoire -- 19e siècle.; Imprimerie -- Angleterre -- Histoire -- 19e siècle.; Littérature et société -- Angleterre -- Histoire -- 19e siècle.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Authors and publishers; Book design; Illustration of books; Literature and society; Literature publishing; Printing; England; 1800-1899; Electronic books; History; Illustrated works